2023
DOI: 10.3390/ijms24054861
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Energy Metabolism under the Local Control of the Thyroid Hormone System

Abstract: The energy homeostasis of the organism is orchestrated by a complex interplay of energy substrate shuttling, breakdown, storage, and distribution. Many of these processes are interconnected via the liver. Thyroid hormones (TH) are well known to provide signals for the regulation of energy homeostasis through direct gene regulation via their nuclear receptors acting as transcription factors. In this comprehensive review, we summarize the effects of nutritional intervention like fasting and diets on the TH syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 175 publications
0
9
0
Order By: Relevance
“…To further dissect the functional relevance of TRα on HSCs during inflammation and fibrogenesis the authors employed single cell RNA sequencing (scRNA‐seq) of TRα −/− mouse embryonic fibroblasts (MEFs) and investigated MCD diet‐induced NASH and liver fibrosis in TRα −/− mice 10 . As anticipated, scRNA‐seq revealed that TRα is involved in inflammatory and many energy dependent signalling pathways including glucose, lipid and protein metabolism 5,10 . Activation of HSCs and transdifferentiation into ECM‐producing myofibroblasts requires an energy‐intensive metabolic reprogramming—thus, this study highlights the relevance of local and cell type‐specific TH activities 5,12,13 .…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…To further dissect the functional relevance of TRα on HSCs during inflammation and fibrogenesis the authors employed single cell RNA sequencing (scRNA‐seq) of TRα −/− mouse embryonic fibroblasts (MEFs) and investigated MCD diet‐induced NASH and liver fibrosis in TRα −/− mice 10 . As anticipated, scRNA‐seq revealed that TRα is involved in inflammatory and many energy dependent signalling pathways including glucose, lipid and protein metabolism 5,10 . Activation of HSCs and transdifferentiation into ECM‐producing myofibroblasts requires an energy‐intensive metabolic reprogramming—thus, this study highlights the relevance of local and cell type‐specific TH activities 5,12,13 .…”
Section: Figurementioning
confidence: 99%
“…gluconeogenesis, glycolysis, glycogen synthesis, lipogenesis, lipolysis, uptake and ß-oxidation of FFA). 5 Approximately 80% of the total liver tissue is occupied by parenchymal liver cells (i.e. hepatocytes).…”
Section: E D I T O R I a L Cell Type-specific Actions Of Thyroid Horm...mentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the relationship between NASH and thyroid function in healthy states is critical for conceptualizing how hypothyroidism perturbs this relation [24,25]. In the liver, thyroid hormones (THs) regulate energy and metabolic homeostasis by modulating the export of lipids from the hepatocyte into the bile and the blood stream, as well as their oxidation and de novo lipogenesis [26].…”
Section: What Has Nash To Do With Thyroid?mentioning
confidence: 99%
“…Few methods address these dual challenges of sample scarcity and low levels, leading to infrequent reports on CSF hormone levels [30]. A further advantage of using LC-MS to quantify TH in CSF is that it can be combined with global assessments of the metabolic state through targeted LC-MS metabolic profiling of central energy metabolism, a process dependent on TH during development and adulthood [8,23,27,[38][39][40][41]. Better detection and reporting of this key hormone in CSF requires a new and sensitive approach, which we describe here.…”
Section: Introductionmentioning
confidence: 99%